Resolving phylogenetic relationships of Delphacini and Tropidocephalini (Hemiptera: Delphacidae: Delphacinae) as inferred from four genetic loci - Yi-Xin Huang (Nature Portfolio, 2017)
Abstract This paper explores the phylogeny of the delphacid subfamily Delphacinae based on nuclear ribosomal and mitochondrial DNA sequences of four genetic loci (16S rDNA, 28S rDNA, Cytochrome oxidase I and Cytochrome b). Maximum likelihood and Bayesian analyses yield robust phylogenetic trees. The topologies support the monophyly of Delphacinae and its basal split into three tribes, and provisionally support subdividing Delphacini into three clades, including a more broadly defined Numatina. The tribe Tropidocephalini is divided into two clades. In addition, Paranectopia is transferred from Tropidocephalini to Delphacini and Harmalia syn. nov. is regarded as a junior synonym of Opiconsiva. The genera Bambusiphaga, Megadelphax and Muirodelphax are found to be paraphyletic. The estimated time to the most recent common ancestor of Delphacinae is roughly at 90 million years ago in Late Cretaceous.